The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/ncomms14993
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalysed retro-hydroamidocarbonylation of aliphatic amides to olefins

Abstract: Amide and olefins are important synthetic intermediates with complementary reactivity which play a key role in the construction of natural products, pharmaceuticals and manmade materials. Converting the normally highly stable aliphatic amides into olefins directly is a challenging task. Here we show that a Ni/NHC-catalytic system has been established for decarbonylative elimination of aliphatic amides to generate various olefins via C–N and C–C bond cleavage. This study not only overcomes the acyl C–N bond act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 60 publications
(64 reference statements)
0
30
0
Order By: Relevance
“…Interestingly,i n2 017, Shi and co-workersr eported an ickelcatalyzed retro-hydroamidocarbonylation of aliphatic amides into olefinst hrough amide NÀCa ctivation (Scheme 44). [82] This methodo ffered broad functional-group tolerance andt he opportunity for late-stage olefination in complex molecules. Mechanistic studies revealed the involvement of ar adicalp rocess.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…Interestingly,i n2 017, Shi and co-workersr eported an ickelcatalyzed retro-hydroamidocarbonylation of aliphatic amides into olefinst hrough amide NÀCa ctivation (Scheme 44). [82] This methodo ffered broad functional-group tolerance andt he opportunity for late-stage olefination in complex molecules. Mechanistic studies revealed the involvement of ar adicalp rocess.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…181 A 2017 report by Shi and co-workers features the description of a mechanistically intriguing retro-hydroamidocarbonylation of Boc-activated amides (304), leading to the facile formation of a wide array of olefinic products (306) through b-hydride elimination of 305 (Scheme 46b). 182 Further privileged amides in selective transformations properties for (selective) transition metal-catalysed or even metalfree transformations. Azetidine amides (307) represent such a privileged class of amides, as Szostak and co-workers were able to show that their treatment with organolithium and Grignard reagents in the absence of any catalyst selectively affords the corresponding ketones (Scheme 47a).…”
Section: Smi 2 -Mediated Functionalisationmentioning
confidence: 99%
“…Shi and co‐workers studied an amide‐to‐olefin conversion . This reaction proceeds by the oxidative addition of a nickel(0) catalyst to the amidic bond, which, after the decarbonylative process, leads to the corresponding alkyl–nickel(II).…”
Section: N‐boc‐amidesmentioning
confidence: 99%
“…Shi and co-workers studied an amide-to-olefin conversion. [64] This reaction proceeds by the oxidative addition of an ickel(0) catalystt ot he amidicb ond, which,a fter the decarbonylative process, leads to the corresponding alkyl-nickel(II). The latter undergoes b-H elimination to generate the corresponding olefin.L ike the other nickel catalytic systems, an NHC-type ligand is required and, in particular,a ne lectron-rich one.…”
Section: Amide-to-olefin Conversionmentioning
confidence: 99%